Kewenangan Komisi Penyiaran Indonesia Daerah Jawa Tengah Dalam Pengawasan Siaran Iklan Kampanye Pemilu 2024 Di Televisi - Utomo, Atok Dadyo; Kukuh Sudarmanto; Muhammad Junaidi; Zaenal Arifin; Bahmid Bahmid (Journal Juridisch, 2025)
This study aims to analyze the authority of the Regional Indonesian Broadcasting Commission (KPID) of Central Java in supervising television broadcasts of campaign advertisements for the 2024 General Election. The urgency of this research lies in the ongoing violations of broadcast neutrality, which have the potential to influence public opinion and undermine the quality of democracy. The method employed is normative juridical with a statutory approach, supported by interview data from KPID Central Java. The findings indicate that KPID’s authority complies with the eight principles of legality and has proven to be fairly effective through the fulfillment of five factors in broadcast law enforcement. This study differs from previous research as it specifically evaluates the role of KPID in the context of the 2024 Election and the challenges posed by contemporary broadcasting regulations. In conclusion, KPID’s supervision contributes to the creation of democratic and high-quality broadcasts, although institutional strengthening and regulatory support are still required. This research contributes to the development of broadcasting law studies while also providing recommendations for the government and KPI to reinforce both the authority and effectiveness of election broadcast supervision in the future. Penelitian ini bertujuan menganalisis kewenangan Komisi Penyiaran Indonesia Daerah (KPID) Jawa Tengah dalam pengawasan siaran iklan kampanye Pemilu 2024 di televisi. Urgensi penelitian didasarkan pada masih ditemukannya pelanggaran netralitas siaran yang berpotensi menggiring opini publik dan mengancam kualitas demokrasi. Metode yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan yang didukung data wawancara dengan KPID Jawa Tengah. Hasil penelitian menunjukkan bahwa kewenangan KPID telah memenuhi delapan prinsip legalitas hukum dan terbukti cukup efektif melalui pemenuhan lima faktor penegakan hukum penyiaran. Penelitian ini berbeda dari studi sebelumnya karena secara khusus mengevaluasi peran KPID dalam konteks Pemilu 2024 serta tantangan regulasi penyiaran kontemporer. Kesimpulannya, pengawasan KPID mendukung terciptanya siaran demokratis dan berkualitas, namun masih memerlukan penguatan kelembagaan dan dukungan regulasi. Penelitian ini berkontribusi pada pengembangan kajian hukum penyiaran sekaligus memberikan rekomendasi bagi pemerintah dan KPI untuk memperkuat kewenangan serta efektivitas pengawasan penyiaran Pemilu di masa mendatang.